Micro-Fabricated Compact Extrinsic Fabry-Perot Sensor for In-Situ Harsh Environment Acoustic Measurement - Qi Xi; Binghe Ma; Zhiyong Tian; Ruofei Li; Yinan Wang; Zhibo Ma (IEEE Photonics Journal)
This paper presents a compact extrinsic Fabry-Perot acoustic sensor. The key component of this sensor is a SOI chip with acoustic sensing Si diaphragm of 5 mm diameter and $2\,{\rm{μ m}}$ thickness, which is obtained by micro fabrication process. Acoustic calibration experiment indicates that the sensor exhibits a frequency response range over 100 Hz-20 kHz, and a sensitivity of ${95}\,{\rm{.73mV/Pa}}$ . High temperature plane wave tube is established for experiment that simulates the acoustic field in harsh environment, indicating that the sensor is able to realize acoustic sensing with ambient temperature up to ${589}\,^° C$ . The prospect of our proposed sensor is realizing multi-point, in-situ acoustic measurement in harsh environment of aerospace engine internal flow field, enabled by its batch fabrication process and high compactness as well as sensitivity, which we believe will shows great potential in significant industrial domains.